2019
DOI: 10.11606/issn.2317-0190.v26i4a168675
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas osteomioarticulares em bombeiros militares do Distrito Federal

Abstract: Objetivo: Verificar a prevalência de sintomas osteomioarticulares em bombeiros militares do Distrito Federal. Metódo: Trata-se de um estudo transversal, realizado com bombeiros militares de idades entre 18 e 55 anos. Foi utilizado o Questionário Nórdico de Sintomas Osteomusculares e os participantes relataram a ocorrência dos sintomas nos 12 meses e nos sete dias precedentes à entrevista, bem como os afastamentos das atividades no último ano. Os dados foram tabulados no programa Microsoft Excel 2016 e foi feit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Publications on sleep parameters in Brazilian military personnel, in addition to being scarce, involve a reduced sample size and are not uniform in terms of the method used, making comparisons difficult. However, our results were similar to those of Iahnke et al (2022), 29 Oliveira (2020) 30 and Pinto et al (2018), 31 who found 66.2%, 81.59% and 63.6% prevalence of poor sleep quality using the PSQI in army personnel, firefighters and military police, respectively. The fact that our study took place shortly after the COVID-19 pandemic may have contributed to the high prevalence of poor sleep, showing a final reflection of social changes such as confinement and social isolation, less exposure to sunlight, reduced activity physical activity, and increased stress.…”
Section: Discussionsupporting
confidence: 91%
“…Publications on sleep parameters in Brazilian military personnel, in addition to being scarce, involve a reduced sample size and are not uniform in terms of the method used, making comparisons difficult. However, our results were similar to those of Iahnke et al (2022), 29 Oliveira (2020) 30 and Pinto et al (2018), 31 who found 66.2%, 81.59% and 63.6% prevalence of poor sleep quality using the PSQI in army personnel, firefighters and military police, respectively. The fact that our study took place shortly after the COVID-19 pandemic may have contributed to the high prevalence of poor sleep, showing a final reflection of social changes such as confinement and social isolation, less exposure to sunlight, reduced activity physical activity, and increased stress.…”
Section: Discussionsupporting
confidence: 91%